PANTUN MASYARAKAT DI NAGARI PAINAN TIMUR KECAMATAN IV JURAI KABUPATEN PESISIR SELATAN - Handayani, Yelsi; Nasution, Bakhtarudin; Zulfadhli, Zulfadhli (Universitas Negeri Padang, 2017)
This article aims to describe the structure and function of rhyme society in East Painan Nagari, District IV Jurai, South Coastal District. Study the theory used in this research, among others; (1) understanding of folklore, (2) the folklore and oral literature, (3) the nature of the poem Minangkabau, (4) the kinds of quatrain Minangkabau, (5) the characteristics of the poem, (6) the structure of the poem, (7) the function of rhyme Minangkabau , Pantun Nagari community in East Painan has a physical structure and inner structure. The physical structure consists of: (1) use of diction, (2) using images, (3) use concrete words, (4) using figurative language, (5) using rhyme a, i, u, e, o, h, m, n, ng, and k and Ritma said. Inner structure consists of: (1) theme, (2) feeling, (3) the tone and atmosphere, (4) Â mandate. Function of rhyme society in east Painan Nagari, District IV Jurai, South Coastal Dict consists of: (1) as a means of communication, (2) as an identity Minangkabau society, (3) as flowers decorate tradition of Minangkabau society, (4) as a means to preach, (5) as a means to educate, (6) as the embodiment of traditional, (7) as symbols of Minangkabau culture, (8) to excite and motivate the heroic values of Minangkabau society, (9) to humanize humans.Â Keywords: Pantun, structure and function, oral tradition